Level of knowledge, awareness and attitude among plantation workers on occupational safety and health procedure at the work place in Rubber Industry Smallholders' Development Authority (RISDA) Semaian, Sekijang Segamat, Johor / Mohamad Luqman Sahap - Sahap, Mohamad Luqman (Faculty of Plantation and Agrotechnology, 2015)
The purpose of this study is to evaluate level of knowledge, awareness and attitude of plantation workers as well as to identify the existence of a relationship of mutual influences between factor of knowledge, awareness and attitude towards OSHA practice and determine for the most dominant factors that influences the level of practices of OSHA. The subjects of this study consisted of 124 plantation workers those attached to oil palm plantation,rubber plantation and nursery whereby directly involved in conducting the works on the plantation at RISDA Semaian Sekijang, Segamat Johor had been selected using simple random sampling. This study is in the form of survey, using one instrument for data collection i.e. Questionnaire. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 22. The data obtained were then analyzed using the descriptive statistic, correlation and multiple regressions. Analysis descriptive showed that respondents have a high level of knowledge and awareness towards OSHA procedure when the overall mean score of 4.37 and 4.02 respectively. Whereas, for the attitude factor, plantation workers have a positive attitudes when recorded an overall mean score of 4.52. The result of the study also revealed that there was a positive correlation between factor of knowledge, awareness and attitude towards OSHA practice. Meanwhile their significant value is 0.000 which is smaller than the significant level of 0.01 (2-tailed). The result also revealed each of the aspects namely knowledge, awareness and attitudes had a significant effects on OSHA practices when r² value obtained was .728 explained that 72.8% of the variance associated with the OSHA practices. The analysis results showed that the most dominant variable towards OSHA practice is awareness with the β value is 0.367, followed by a factor of knowledge with the β value is 0.342 and attitudes with the β value is 0.201. Chronologically, the factors that most influence the level of practices of plantation workers on OSHA at workplace are the awareness, knowledge, and attitudes. Overall, this study shows that the level of practices of Occupational Safety and Health among plantation workers who worked in RISDA Semaian, Sekijang Segamat Johor is at a high level.